2019
DOI: 10.2147/cmar.s207677
|View full text |Cite
|
Sign up to set email alerts
|

<p>Berberine induces apoptosis in non-small-cell lung cancer cells by upregulating miR-19a targeting tissue factor</p>

Abstract: BackgroundBerberine (BBR) from the widely used Chinese herbal medicine Huanglian has an array of pharmacological and biochemical properties, including anti-neoplastic activity. However, the specific mechanisms underlying these properties are unknown. The aim of this study was to explore the anti-tumor mechanisms of BBR in non-small cell lung cancer (NSCLC).MethodsThe effects of BBR on NSCLC tumor development and programmed cell death were investigated both in vivo and in vitro. Luciferase reporter assays were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…[ 18 ]. Hong et al described that berberine reduced the phosphorylation of JNK in gastric cancer cells [ 19 ], but the influence of berberine on kinases is strongly dependent on many conditions [ 20 , 21 , 22 ].…”
Section: Berberine In Cardiovascular and Metabolic Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 18 ]. Hong et al described that berberine reduced the phosphorylation of JNK in gastric cancer cells [ 19 ], but the influence of berberine on kinases is strongly dependent on many conditions [ 20 , 21 , 22 ].…”
Section: Berberine In Cardiovascular and Metabolic Diseasesmentioning
confidence: 99%
“…The effect depends on the type of cell. Berberine activates MAPK in human colon cancer cells [ 61 ], non-small cell lung cancer cells and human hepatoma cells (HepG2) [ 20 , 21 ]. In turn, in human HeLa cervical carcinoma cells, berberine enhances phosphorylation of JNK and ERK1/2 but inhibits phosphorylation of p38 MAPK [ 62 ].…”
Section: Anticancer Activity Of Berberinementioning
confidence: 99%
See 1 more Smart Citation
“…(2015) reported similar results that berberine-induced apoptosis was mediated by activation of the p38 MAPK signaling pathway via the death receptor ligand FOXO3a, p53, and FasL. In another study, berberine also promoted the rate of apoptosis of NSCLC cells by the suppression of the MMP-2, Bcl-2/Bax, and modulating the miR-19a/TF/MAPK signaling pathway ( Chen et al., 2019 ).…”
Section: Resultsmentioning
confidence: 78%
“…Recent findings have demonstrated that BBR exhibits antitumor activity through the inhibition of cancer cell progression and migration and the induction of apoptosis in several types of cancer [ 99 102 ]. Abrams et al have reported that also BBR derivatives exert anticancer proprieties; indeed the treatment with a panel of BBR derivatives (NAX compounds) in three different PDAC pancreatic cancer cell lines, inhibited proliferation, and suppressed colony formation [ 103 ].…”
Section: Berberine and Cancermentioning
confidence: 99%